Business basics : workbook - Grant, David; McLarty, Robert (Oxford : Oxford University Press, 1995)
You and your company. Preparing a trip. Away on business. Visiting a company. New developments. Arrangements. Describing and comparing. Success stories. Dealing with problems. People at work. Getting a job. Working in the nineties.
Keywords: English language; Business English; English language -- Business English